“Only One Way Out”-Partners' Experiences and Grief Related to the Death of Their Loved One by Suicide or Physician-Assisted Dying Due to a Mental Disorder - Snijdewind, Marianne C.; de Keijser, Jos; Casteelen, Gerty; Boelen, Paul A.; Smid, Geert E. (Frontiers in Psychiatry, 2022)
Background Previous research has provided insight into the grief of suicide survivors, but little is known about grief following physician-assisted dying (PAD), and no prior study specifically focused on grief following PAD due to a mental disorder. The current study aims to increase insight into experiences preceding PAD or suicide of a loved one due to a mental disorder and their impact on mental health symptoms. Methods We performed a survey study and in-depth interviews with 27 bereaved life partners. The deceased had been in treatment for mental disorders and had died by PAD (n = 12) or suicide (n = 15). Interviews explored grief experiences and experiences with mental health care. In the survey, we assessed self-reported symptoms of grief, posttraumatic stress, anxiety, depression, quality of life, and impairments in social and occupational functioning. Results All participants reported generally low levels of mental health symptoms. Longer time since death and death by PAD were associated with lower grief intensity. Interviews showed various degrees of expectedness of the partners’ death, and a varying impact of being present at the death on bereaved partners. Conclusion Expectedness of the death of the partner, absence of suffering of the partner at the time of dying, and presence of physician support may in part explain the protective effects of PAD against severe grief reactions. Physicians considering their position regarding their personal involvement in PAD due to a mental disorder could take grief reactions of the bereaved partner into account.